Faderskapspresumtionen - En föråldrad huvudregel - Möllebäck,Seth (2024)
The project audits the presumption of fatherhood in the Swedish legal system and related legal areas. This is done to evaluate if the presumption is fulfilling its purpose. To achieve this a thorough analysis of the subject is conducted. The history of the legal area is explored, and the applicable law is reviewed. The interests in of the different involved parties such as the parents and the public have been defined. This also relates to the principle of the best interest of the child. Historically children have been defined by if they were conceived within or outside of wedlock. Today this is not the case and is almost completely out of the legal system. As time progressed, the rights of children have come to be regarded as the most important part of family law. How parenthood is estab-lished has also changed over the years. The main rule of determining fatherhood has been through the presumption of fatherhood. This presumption establishes that the husband of a woman who gives birth to a child, is to be assumed to be the father of said child. When the presumption is not applicable, fatherhood is declared through a confirmation or a verdict. The woman who gives birth to a child is regarded as the mother of the child. The best interest of the child regarding the subject is to ensure two parents for the child as far as possible. The interests to regard in the legislative process is that of the public, the par-ents as well as the child. It is in the interest of the public to legislate in an equal manor, and to live up to the international codes it has promised to up-hold. The interest of the parents is to ensure that the right parents are declared parents to the right child, as it is of great importance if the parents want to care for their children. The code of conduct is that parents are to care for their chil-dren. If this is not done properly, the social services steps in to make sure the children are ensured their rights. In the legislative process, it has been discussed both to remove and expand the fatherhood presumption. To remove the presumption has historically been associated with an additional and unnecessary workload for the public. To expand the presumption has been problematic, as domestic partners are not registered and would presumably lead to unclear and faulty results. In recent years a new presumption of parenthood has been introduced which include same-sex couples who are married or registered partners. A new and simpler form of fatherhood confirmation has also been introduced. To conclude, the presumption of fatherhood is outdated and in need of revi-sion. A new main rule for establishing parenthood should be considered. In my opinion the simpler form of confirmation is one of the better options that would be more in line with the best interests of the child according to me.
Keywords: Familjerätt